High Power 4.2-Cycle Mid-Infrared Pulses From a Self-Compression Optical Parametric Oscillator - Jintao Fan; Chenglin Gu; Ruoyu Liao; Lu Chai; Minglie Hu (IEEE Photonics Journal)
We demonstrate the generation of few cycle mid-infrared (MIR) pulses from a self-compressed optical parametric oscillator (OPO), synchronously pumped by a 105 fs Yb3+ doped fiber laser system. By using a ring cavity design, 4.2-cycle (45.3 fs) MIR pulses at a central wavelength of 3250 nm (with a 10-dB bandwidth of 648 nm) are obtained in a simple, practical, and compact configuration. Detailed theoretical analysis and numerical simulation are performed to better understand the self-compression mechanism in such an OPO cavity. In addition, when pumped at 3.8 W, the OPO delivers idler output power up to 330 mW and the corresponding pump depletion is 74.7%.